Innovation Management in Developing Economies: Experiences from Ghana's Banking Industry. - Baffoe, Dinah (2013)
Globalization in the world economy has created a lot of competition in the global market. This has compelled most organizations to use innovation to gain strategic advantage. Innovation has also transcended into the business environment of developing economies. Owing to this, most organizations have had to develop innovation management capabilities to enable them compete both in their home markets and on the international market. The purpose of this exploratory and explanatory research was to unearth evidence of innovation management in developing economies by drawing on experiences from Ghana’s banking industry. By using online survey and structured interview,the feasibility of some innovation management models was assessed employees in Ghana’s banking industry. Due to fierce competition in the banking industry corporate strategy was ranked highest as a model for managing innovation within most banks in Ghana. The findings also revealed that the least ranked innovation management model was linkages which indicated a low level of external networking in the industry. The findings of this research emphasize the need for organizations in developing economies to develop their external linkages not just with consumers but other external parties to manage innovation. From these results, managerial implications and recommendations for future research was offered.